Step-by-step explanation:
x²-y²=12
(x-y)(x+y)=12
but x-y=4
4(x+y)=12
x+y=12/4
x+y=3
lets make x the subject of the formula
x=3-y
since x-y=4
(3-y)-y=4
3-y-y=4
-2y=1
y=-1/2
then x=3-y
x=3-(-1/2)
x=(6--1)/2
x=7/2
therefore; x²+2xy+y
=(7/2)²+2×7/2×-1/2+(-1/2)
=49/4-7/2-1/2
=(49-14-2)/4
=33/4
=8.25
=8
He counted too far. 5 x 2 is 10. He counted up to 25 which is 5 x 5, past what he is looking for.
Answer:67,200
Step-by-step explanation: You multiply length×width×height.
Sorry If I am Wrong.
Answer:
The answer would be B.
Step-by-step explanation:
Firstly, you need to cancel out equal terms.
That would leave you with: 9=-6.
That of which is false, even so we have broken it down to its limit. Therefore, that is the only option without a solution.